BACKEND API DATA PROTECTION MENGGUNAKAN JWT TOKEN DAN ALGORITMA AES 256-BIT DENGAN BAHASA PEMROGRAMAN GOLANG - Prasetya, Agustinus Bayu; Suharjo, Imam (Universitas Lampung, 2025)
Data security is a critical concern in the development of web-based applications and backend APIs, particularly in protecting sensitive information from unauthorized access. This research aims to integrate Advanced Encryption Standard (AES) 256-bit for data encryption and JSON Web Token (JWT) for user authentication, developed using the Go programming language. The methodology employed is Research and Development (R&D), encompassing stages of requirement analysis, system design, implementation, and testing. The results show that combining AES 256-bit and JWT provides a dual-layer security mechanism, ensuring data integrity and confidentiality during storage and transmission. This solution proves effective for high-security applications such as e-commerce, healthcare, and online examinations. Additionally, the system offers seamless integration with third-party applications, promoting ease of adoption without compromising security. The study concludes that this integrated approach enhances data protection and facilitates secure API interactions across various platforms